Analysis of mechanical property of electrically assisted friction stir welding to enhance the efficiency of joints. (2021) - Sengupta, Kaushik; Kr Singh, Dilip; Mondal, Arpan K; Bose, D.; Ghosh, Biswajit
Abstract: The concept of Friction Stir Welding (FSW) technique was invented in year 1991 and since then many research have been done in the same field. To utilize the technique in various materials, many additional heat sources had been tested successfully and many such hybrid FSW methods came up. Electric Resistance Friction Stir Welding has been invented as one of the hybrid technology and produces less tear and wear of the tool with fewer defects of the joint produced. This study has been done to find the effect of secondary source of energy by electric assistance to FSW for improving the efficiency of the weld and to study the effect of various process parameters to improve the property of the weld joint of CS to IS 2062 Grade B. Design of Experiment has been applied to study the influence of the process parameters viz tool speed (rpm), electric current (Amps) and feed on the UTS of the weld. The joint has also been tested for checking the variation of the weld efficiency and hardness of the joint due to change in process parameters. The optimization of the process parameters has been done to obtain maximum Tensile strength, weld efficiency and hardness. The results of the optimization has been found to be indicating that due to the effect of addition of secondary heat source of electric current, the welding efficiency and hardness value has been found higher than the specimen joined without the secondary source.